Marriage Immigration and Gender in South Korea: Accounting for Gender Disparities in International Marriages - Kim, Junmo (Animo Repository, 2012)
Recent studies on immigration in East Asia are focusing on female marriage immigration, the migration of large numbers of women from developing countries to marry men from industrialized countries like South Korea. Typically lost in the discourse however, are international marriages involving foreign grooms, once the more dominant trend in South Korea before the mid-1990s. This article explains how trends in international marriages in South Korea reversed in the mid- 1990s and how marriages involving the two genders differ in their drivers and characteristics. Both phenomena are examined in the context of neo-classical economics and push-pull theories of migration, hypergamy, homogamy, demographic transition, changing social norms, and state policies. The large scale migration of foreign brides to South Korea, or marriage immigration, is driven by demographic factors, institutionalized support, and the rise of a commercial marriage industry. Marriages involving foreign men do not share the characteristics of marriage migration, its drivers are less clear, nor is it supportedby the state and Korean society.